Co-stimulation with an olfactory stimulus increases arousal responses to trigeminal stimulation - Stuck, B. A.; Baja, J.; Lenz, F.; Herr, Raphael M.; Heiser, Clemens (Neuroscience, 2011)
An interaction of the intranasal chemical trigeminal and the olfactory system has previously been described. Intranasal chemical trigeminal stimulation during sleep leads to a dose-dependent increase in arousal reactions while pure olfactory stimuli are not able to trigger arousals or awakenings during sleep, regardless of the concentration used. The aim of the study was to assess whether co-stimulation with an olfactory substance increases arousal responses to intranasal chemical trigeminal stimulation. Experimental procedures: Five young healthy, normosmic volunteers of both sexes participated in the trial and 20 nights of testing were performed. For intranasal chemical trigeminal stimulation, CO2 was administered at 40% v/v and at 0% as a control stimulus. For olfactory co-stimulation, H2S was used at a concentration of 8 ppm. To compare the specific nasal chemical trigeminal/olfactory interaction with an interaction between an olfactory stimulus and peripheral somatosensory stimulation, an electrical stimulation protocol at the forearm was used with and without olfactory co-stimulation. Results: Chemical trigeminal stimulation with 40% CO2 led to an increase in arousal frequency compared to the control stimulus, which was most pronounced in light sleep. Co-stimulation with H2S was associated with higher arousal frequencies and shorter arousal latencies compared to isolated chemical trigeminal stimulation. The differences between the three study conditions were statistically significant for light sleep. Increasing electric stimulus concentration was associated with an increase in arousal frequency, again most pronounced in light sleep. Co-simulation with the olfactory stimulus did not lead to a systemic effect with regard to arousal reactions. Conclusions: The present results confirm the close interaction of the olfactory and chemical trigeminal system and support the idea that this interaction takes place at an early stage of processing. © 2011 IBRO.
CRIS-Team Scopus Importer:2022-11-28
Keywords: Arousals; Chemosensation; Interaction; Olfaction; Trigeminal